Nanomaterials Imaging Techniques, Surface Studies, and Applications Selected Proceedings of the FP7 International Summer School Nanotechnology: From Fundamental Research to Innovations, August 26-September 2, 2012, Bukovel, Ukraine - Fesenko, Olena; Yatsenko, Leonid; Brodin, Mikhaylo (Springer Proceedings in Physics,, 2013)
This book presents cutting-edge research on a wide range of nanotechnology techniques and applications.  It features contributions from scientists who participated in the International Summer School "Nanotechnology: From Fundamental Research to Innovations" in Bukovel, Ukraine on August 26 - September 2, 2012 funded by the European Commission FP7 project Nanotwinning implemented by the Institute of Physics of National Academy of Sciences of Ukraine and partner institutions: University of Tartu (Estonia), European Profiles A.E. (Greece), University of Turin (Italy) and Université Pierre et Marie Curie (France).  Worldwide experts present the latest results on such key topics as microscopy of nanostructures; nanocomposites; nanostructured interfaces and surfaces; nanooptics; nanoplasmonics; and enhanced vibrational spectroscopy.  Imaging technique coverage ranges from atomic force microscopy and spectroscopy, multiphoton imagery, and laser diagnostics of nanomaterials and nanostructures, to resonance Raman and SERS for surface characterization, and scanning tunneling microscopy of organic molecules.  The breadth of topics highlights the exciting variety of research currently being undertaken in this field and suggests exciting opportunities for interdisciplinary collaboration and future research. Presents microscopy, spectroscopy and laser imaging techniques for nanomaterials and nanocomposites Covers state-of-the-art advances in areas suc h as nano-bio architectures, metal nanostructures and active materials, and chemical preparation of graphene Represents essential reading for advanced undergraduate and graduate students through practicing university and industry researchers.